Teaching New Vocabularies Through Educational Games to Enhance Better Understanding of Literary Terms in EFL Classes A Case Study of First Year University Students of Department of English at Ammar Thelidji - Benali, Samiha; Benaya ,Hala; Nouioua, Amira (Faculty of Letters and Foreign Languages Department of English, 2019)
This study aims to investigate the enhancement of English vocabulary of literary and how these games facilitate learning new literary terms texts through games, for first year students of English literature department. We hypothesize that if vocabulary teaching is handled with care through effective listening or reading, and motivation involved in reading a lot of literary texts and practicing related words within games, the problem of lack of comprehension will be reduced. To reach such an aim, we administer a questionnaire of number of statements to participants at English Department University of Laghouat with reference to first year students of English Language and Literature in particular, for the academic year 2018-2019.The results reveal that educational games constitute effective methods to enrich vocabulary background as much as possible, and the majority of 1st year students are agree with the idea of applying educational game in their literature courses